Precocious hand use preference in reach‐to‐eat behavior versus manual construction in 1‐ to 5‐year‐old children. Issue 8 (5th November 2012) - Sacrey, Lori‐Ann R.; Arnold, Benjamin; Whishaw, Ian Q.; Gonzalez, Claudia L.R.
Abstract The variation in hand use as a function of task and developmental age poses a problem for understanding how and when "handedness, " preferred use of one hand, develops. The present cross‐section study is the first to contrast hand preference use for the natural and frequently used reach‐to‐eat movement with a constructional task that requires a very similar reach‐to‐grasp movement. Thirty children between the ages of 1 and 3 years completed an eating task, in which they grasped small food items (Cheerios™ or Froot Loops™) that they brought to the mouth for eating. Thirty children between the ages of 3 and 5 years completed the construction task, in which they grasped LEGO® pieces to construct 3D models. Hand use preference for grasping in the eating and construction tasks was calculated by comparing the percentage of grasps made by the right hand and by the left hand. There were two main findings: First, right hand preference for grasping in the eating task is present as early as 1 year of age, whereas right hand preference for grasping in the construction task does not develop until 4 years of age. Second, right hand preference for grasping is greater in the eating than in the construction task. The results are discussed in relation to the idea that a consideration for task constraints (e.g., unimanual vs. bimanual; eating vs. construction; natural vs. praxic) should be incorporated into the experimental design when measuring hand use in children. © 2012 Wiley Periodicals, Inc. Dev Psychobiol 55: 902–911, 2013.